In-conclusion: resisting resolution in recent paintings by Penny Siopis - Koch, Renee Lesley (My University, 2012)
This research report focuses on two parts of perception, namely the gathering of visual data (looking) and the interpretation of such data (seeing). I examine the way that materiality, in recent paintings by Penny Siopis, functions to resist the insistent narrative image, by producing ambiguity, indeterminacy or imprecision. In my practical research I explore ways to fore-ground looking, to resist seeing the representational image and to create a state of perceptual tension, which engages the viewer in re-looking.
M.A. University of the Witwatersrand, Faculty of Humanities (Fine Art), 2012